Thinking big [soundrecording] the keys to personal power and maximum performance - Tracy, Brian (Simon & Schuster, 1996)
Discusses recognizing critical success factors and why they are vital to personal and professional success, developing the mindpower of a genius, harnessing the powers of the subconscious mind to perform at higher levels, and identifying unique abilities and talents.